The Minutemen and their world - Gross, Robert A. 1945- (Picador, Farrar, Straus and Giroux, 2022)
"The classic work on one town's American Revolution--now with a new preface and afterword by the author"--
"Originally published in 1976 by Hill and Wang.
Keywords: Geschichte; Amerikanische Revolution; Concord, Mass.; Concord (Mass.) / History / 18th century; Concord, Battle of, Concord, Mass., 1775; Concord (Mass.) / Social conditions / 18th century; Minutemen (Militia) / Massachusetts; Minutemen (Militia); Social conditions; Massachusetts; Massachusetts / Concord; 1700-1799; History